Alienated History, Alien Events. - Gavrilin, Andrey (Problems / Problemos, 2025)
Human history is largely shaped by human actions - most historical events are man-made, despite nature also playing a role. Yet, people often see these events as alien, as if shaped by something or someone else. For instance, many view man-made climate change as unrelated to humanity, while non-deniers often see no way to influence it collectively. This disconnection mirrors Marx's concept of alienation. I argue that alienation applies not only to labour but to all human-made outcomes, including historical events - this is a phenomenon I refer to as historical alienation. Estrangement from economic and political processes can lead people to feel that history is beyond their control. This perspective helps explain presentism and passivity in the face of crises, suggesting that increasing conscious participation in collective decision-making could mitigate these effects.